Evaluation of citizen science contributions to radon research. (October 2021) - Martell, Meritxell; Perko, Tanja; Tomkiv, Yevgeniya; Long, Stephanie; Dowdall, Alison; Kenens, Joke
Abstract: In order to reduce lung cancer due to radon exposure situations, not only authorities and organisations but also citizens may meaningfully contribute to radon mitigation actions. Citizen science (CS) initiatives are recognised for their scientific, societal and policy value related to environmental issues. The purpose of this paper is to identify which CS initiatives in the field of radon exist and evaluate to what extent these CS initiatives contribute to radon research and/or radiation protection from radon. We conducted a systematic review of internet pages and scientific literature (September–December 2020) as well as expert consultation to help us identify and assess CS initiatives on radon (September 2020–February 2021). The ten principles of the European Citizen Science Association have been used as a starting point to develop indicators for the analysis of CS contributions to radon research. The results show that there are at least eight CS initiatives in the world contributing to radon related research which comply, to some degree, with each of the ten principles. In all these initiatives citizens contributed or are contributing meaningfully to radon testing and measurements. However, most of them apply the simplest form of participation (crowdsourcing) and only one focuses on radon mitigation. Moreover, unlike CS initiatives in other environmental areas, those focusing on radon are always led by the authorities and/or universities, in a top-down manner. Yet, results confirm that both the experts in radon-related fields and the citizen scientists from radon prone areas benefit from taking part in radon CS initiatives. Experiences and lessons learned in radon related to CS initiatives are identified and discussed in order to inspire future CS initiatives potentially contributing to reducing exposure to radon as well as to the implementation of national radon action plans. Highlights: Systematic review to assess citizen science initiatives on radon research. Key contributions to radon measurements from citizen science. Recommendations for future radon research using the citizen science approach.